Ameliorative effect of rhizobacteria Bradyrhizobium japonicum on antioxidant enzymes, cell viability and biochemistry in tomato plant under nematode stress - Roohi Sharma; Nitika Kapoor; Puja Ohri (Scientific Reports)
Abstract Root Knot Nematode (Meloidogyne incognita) is a major agricultural pest that significantly reduces crop yield. This study investigates the nematicidal potential of Bradyrhizobium japonicum strain 11477 against M. incognita to regulate its pathogenicity in Solanum lycopersicum. Tomato seeds were treated with bacterial cells and supernatant, grown under controlled conditions and later infested with nematode juveniles (5J2/seedling). After 10 days, nematode infestation led to reduced seedling growth, lower root and shoot biomass and decreased photosynthetic pigments. It also triggered oxidative stress, as indicated by elevated stress markers. Enzymatic and non-enzymatic antioxidants along with phenolic compounds showed increased activity in response to nematode-induced stress. However, B. japonicum treatment significantly reduced gall formation, improved plant growth and enhanced biochemical and histochemical attributes. Rhizobacteria also alleviated stress indices, strengthened antioxidant defenses and increased metabolite production. Confocal microscopy revealed hydrogen peroxide localization, glutathione content and nuclear and membrane damage in root apices, correlating with plant defense responses. This study highlights B. japonicum as a potent biocontrol agent that enhances plant growth and resilience against M. incognita. Notably, this is the first report on the impact of a leguminous rhizobacterium on a non-leguminous tomato plant, providing new insights into its potential for sustainable pest management.